2014
DOI: 10.2105/ajph.2013.301549
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exposure to HCV Among Persons Born During 1945–1965: Prevalence and Predictors, United States, 1999–2008

Abstract: With the high prevalence of HCV among persons born during 1945-1965, the increasing morbidity and mortality associated with HCV, and reductions in liver cancer and HCV-related mortality when HCV is eradicated, it is critically important to identify persons with HCV and link them to appropriate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 39 publications
4
41
1
Order By: Relevance
“…31 At the time, it was estimated that three-quarters of all people living with hepatitis C and 70 percent of all those whose deaths were associated with hepatitis C were in this cohort. 32 This recommendation was appropriate given the high prevalence and cost-effectiveness of birth cohort screening. 33 The hepatitis C epidemic has changed, however, and the greatest incidence of infection is now among young people who inject drugs, due to the tremendous spike in injection opioid use among that population.…”
Section: Discussionmentioning
confidence: 99%
“…31 At the time, it was estimated that three-quarters of all people living with hepatitis C and 70 percent of all those whose deaths were associated with hepatitis C were in this cohort. 32 This recommendation was appropriate given the high prevalence and cost-effectiveness of birth cohort screening. 33 The hepatitis C epidemic has changed, however, and the greatest incidence of infection is now among young people who inject drugs, due to the tremendous spike in injection opioid use among that population.…”
Section: Discussionmentioning
confidence: 99%
“…17 In British Columbia, limited enhanced surveillance data on acute HCV cases between 2000 and 2011 showed 81% reported injecting drugs and 38% had been previously incarcerated. 18 Other, lower risk groups may be a part of the repeat testers' cohort, such as baby boomers this cohort, there is evidence that most infected baby boomers are untested 20 and, thus, would be first-time testers largely excluded from our analysis. We concluded that the incidence trends we have reported are predominantly among PWID.…”
Section: Discussionmentioning
confidence: 99%
“…The revised recommendations were based upon findings from the Chronic Hepatitis Cohort Study of 4,689 HCV-infected persons who completed a survey regarding the reason for their HCV testing. 5 That study found that <25% of the HCV-infected persons had an identifiable risk factor for HCV infection; rather 78% were born during the period between 1945 and 1965. With implementation of this new recommendation, an increase in incident HCV infections is expected.…”
Section: Epidemiology and Screening Of Hcv Infection In The Usmentioning
confidence: 96%